Micropropagation of mature pongamia pinnata pierre - Sujatha, K.; Hazra, Sulekha (In Vitro Cellular & Developmental Biology-Plant, 2007)
Murashige and Skoog's (MS) basal medium with benzylaminopurine (BA), kinetin (KN), zeatin (Z), and thidiazuron (TDZ) were tested for induction of multiple shoots from mature-tree-derived axillary meristems of Pongamia pinnata. Sprouting of buds was 64% on medium devoid of plant growth regulators (PGR). Incorporation of BA, KN, or Z was ineffective in enhancing sprouting frequency or induction of multiple shoots. Sprouting was completely suppressed in the presence of TDZ. Caulogenic buds appeared in nodal meristems of these explants after withdrawal of TDZ. The number of shoot buds was more on explants precultured in higher concentrations. At higher concentrations of this PGR, a swelling developed at the axil. Multiple shoot primordia appeared and differentiated from this swelling after culturing these explants on MS medium for six passages of 2 wk each. Shoots were harvested and cultured on 0.45 mu M TDZ for further proliferation. Primary explants after harvesting of shoots were identified as `stump'. Reculturing of stumps on 0.45 mu M TDZ produced more shoots. This step was followed for six cycles to obtain additional shoots in each cycle. Shoots maintained on 0.45 mu M TDZ elongated and rooted (70%) on growth regulator-free medium. Rooted shoots (65%) survived transfer to a sand/soil mixture. This report describes the protocol for micropropagation of P. pinnata using mature-tree-derived nodal meristems. Recycling of mature stock to produce a stream of useable shoots for subculturing and eventual stabilization is of great value and can possibly be generalized as an isolation protocol especially for woody species. Repeated proliferation of caulogenic buds from the same origin may also find application in rescue of endangered germplasm.
Keywords: Biodiesel; Pongam; Pongamia; shoot differentiation; thidiazuron

Effect of TDZ and 2, 4-D on peanut somatic embryogenesis and in vitro bud development - Joshi, Madhumita; Sujatha, K.; Hazra, Sulekha (Plant Cell Tissue and Organ Culture, 2008)
Failure of peanut somatic embryos to convert into plantlets is attributed to the abnormal development of the plumule. Thidiazuron (TDZ) was effective in the conversion of peanut somatic embryos to plantlets by triggering morphogenetic activity in the abnormal plumules of the rooted somatic embryos. The present study aimed to induce normal embryo differentiation by culturing the embryogenic masses in embryo development medium containing 2,4-D and various concentrations of TDZ. Although this was not achieved due to restricted somatic embryo development in the presence of TDZ, bud-like projections appeared in the embryogenic masses when these were cultured in media containing combinations of 2,4-D and TDZ. These projections developed into buds, which subsequently formed shoots and plantlets. The response varied with the concentration and exposure of TDZ. At lower concentrations, the buds appeared in a defined row in the equatorial region of the explant, and with extended incubation, more and more buds appeared in rows alongside the initial row. Induction of multiple buds in a defined row in this specific site (equatorial region) suggested the presence of potent cells around this region. At higher concentrations, these projections appeared in large numbers spread over the whole upper part of the embryogenic mass starting from the equatorial region. The ability of embryogenic mass to convert into organogenic mass and to produce large number of organogenic buds provides an excellent system for basic studies and for the genetic transformation of peanut.
Keywords: Arachis hypogaea; embyogenic mass; somatic embryogenesis; thidiazuron

Assessment of Pongamia pinnata (L.) - a biodiesel producing tree species using ISSR markers - Sujatha, K.; Rajwade, A. V.; Gupta, V. S.; Hazra, Sulekha (Current Science, 2010)